Sijunzi San alleviates the negative energy balance in postpartum dairy cows by regulating rumen fermentation capacity - Wang, Feifei; Mao, Yongxia; Li, Chenlei; Ma, Yanfen; Guo, Yansheng (Frontiers in Veterinary Science, 2024)
IntroductionPostpartum dairy cows are susceptible to negative energy balance caused by decreased feed intake and the initiation of lactation. Sijunzi San, a famous Chinese traditional herbal formulation, can promote gastrointestinal digestion and absorption and improve disorders of intestinal microbiota. Therefore, we hypothesized that Sijunzi San might alleviate negative energy balance in postpartum dairy cows by modulating the structure of the rumen microbiota and enhancing its fermentation capacity.MethodsLiquid chromatography-mass spectrometry (LC–MS/MS) was utilized in vitro to identify the main active ingredients in the Sijunzi San. Techniques including in vitro ruminal fermentation, gas chromatography, and 16S rRNA high-throughput sequencing were employed to evaluate their effects on the structure of the rumen microbiota. To test their in vivo effects, sixteen postpartum Holstein dairy cows, with similar body condition and parity, were randomly assigned to two groups, with 8 cows per group. The CONT group was fed a basic diet, while the SJZS group received an additional 300 g/d of Sijunzi San along with the basic diet, continuously for 7 days. ELISA and untargeted metabolomics using ultra-high-performance liquid chromatography-tandem mass (UHPLC–MS/MS) were employed to assess the impacts on immunoglobulin levels, fat mobilization, and the blood metabolome in postpartum dairy cows.ResultsDoses of 100 to 500 mg of the Sijunzi San significantly enhanced gas production, microbial protein (MCP), and short-chain fatty acid (SCFA) levels, while notably reducing pH and NH3-N content (p < 0.05), exhibiting a significant dose-dependent relationship. The results revealed that 500 mg of the prescription significantly increased the abundances of the Succiniclasticum and Prevotella genera and notably decreased the abundances of the Christensenellaceae_R-7_group, Muribaculaceae, UCG-005, Comamonas, and F082 genera (p < 0.05). Succiniclasticum and Prevotella showed a significant positive correlation with ruminal SCFAs, whereas UCG-005 exhibited a significant negative correlation with them (p < 0.05). Additionally, Luteolin and Glycitein were significantly positively correlated with Prevotella, while Licochalcone B and Liquoric acid were significantly negatively correlated with Comamonas (p < 0.05). Subsequently, the prescription significantly increased the concentrations of IgA, IgM, and microsomal triglyceride transfer protein (MTTP) in the blood (p < 0.01), while reducing the levels of ketones (KET) (p < 0.05), non-esterified fatty acids (NEFA), and triglycerides (TG) (p < 0.01). Notable alterations were observed in 21 metabolites in the blood metabolome (p < 0.05). Additionally, metabolic pathways associated with linoleic acid metabolism and steroid hormone biosynthesis were significantly affected.DiscussionThe findings suggest that administering Sijunzi San to dairy cows during the postpartum period can ameliorate negative energy balance by stimulating rumen fermentation and modifying the composition and abundance of the rumen microbiota.